Histological Evaluation of Internal Dental Resorption: An Analysis of a Cohort of 50 Cases - Tania Puentes-Morelos; Víctor Simancas-Escorcia; Arnulfo Tarón-Dunoyer; Carlos M. Ardila; Antonio Díaz-Caballero (International Journal of Dentistry)
Objective. This study aimed to perform a histological evaluation of teeth diagnosed with internal root resorption. Materials and Methods. A descriptive study involved the examination of 50 human teeth extracted due to an unfavorable prognosis for retention in the oral cavity. Teeth were preserved in 10% buffered formalin and subsequently subjected to the decalcification process. Masson–Goldner staining was applied for comprehensive histological assessment. Results. In all the 50 teeth examined, resorption gaps within the dentin tissue were identified, accompanied by the presence of reparative cells in the vicinity of these cavities. Marked structural loss and dentin fragmentation were evident, with regions exhibiting fissures and an absence of dentinal tubules. Conclusions. The histological evaluation of 50 teeth diagnosed with internal dental resorption revealed significant structural alterations, including resorption lacunae, the presence of multinucleated osteoclast-like cells, and reparative connective tissue. These findings highlight the complex and multifaceted nature of internal dental resorption. These histological insights provide a deeper understanding of the pathological processes involved in internal dental resorption and underscore the necessity for early detection and intervention to mitigate tooth loss and preserve dental health.